2006
DOI: 10.1109/tasc.2006.870005
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Diffraction Study on Prebending Effects for Bronze Route<tex>$rm Nb_3rm Sn$</tex>Wires Without Reinforcement

Abstract: The critical current, upper critical field and critical temperature of bronze route Nb 3 Sn commercial wires are enhanced by applying a repeated bending strain at room temperature, i.e., "prebending strain". In order to investigate the prebending effects from a viewpoint of a residual strain, axial and lateral residual strains were evaluated directly by neutron diffraction at room temperature. We found that the axial residual strain changes from 0.10% to 0.02 % but the lateral one is unchanged by applying a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…It indicates that thermal stress shows a significant effect in the axial direction. Similar behavior can be seen in strain distribution of the Nb3Sn [10]. In the given direction, the samples A and B showed almost the same residual strain in the Nb 3 Al filament.…”
Section: Residual Strains In Wire With Different Matrixsupporting
confidence: 76%
See 1 more Smart Citation
“…It indicates that thermal stress shows a significant effect in the axial direction. Similar behavior can be seen in strain distribution of the Nb3Sn [10]. In the given direction, the samples A and B showed almost the same residual strain in the Nb 3 Al filament.…”
Section: Residual Strains In Wire With Different Matrixsupporting
confidence: 76%
“…Residual strain of Nb 3 Sn in bronze processed Nb 3 Sn wire has been estimated to be about -0.2 --0.1% at the room temperature by a single-peak analysis in the axial direction [9,10]. The residual strain of Nb 3 Sn was shown to have a significant effect by Cu.…”
Section: Introductionmentioning
confidence: 97%
“…Changes of the axial pre-strain have been reported to occur also under cyclic tensile loading [9] and bending [10] of bronze route strands at RT. A reduction of the axial pre-strain in the A15 phase should cause a measurable increase of after the 2nd cool down, with respect to measured after the 1st cool down.…”
Section: Discussionmentioning
confidence: 97%
“…In the meantime, it has become known that the superconducting properties of Nb 3 Sn strands can be improved by a mechanical treatment at room temperature [2]- [4]. We found that what is called the prebending treatment reduces the residual strain [5], [6].…”
Section: Introductionmentioning
confidence: 80%